Comparative in vitro antibacterial activities of two new oral cephalosporins, ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074). - Chau, P Y (1987)
The in vitro activities of two new oral cephalosporins, ceftetrame (Ro 19-5247) and cefetamet (Ro 15-8074), were tested against 990 clinical bacterial isolates in comparison with that of cephalexin. Both compounds were more active than cephalexin against gram-negative bacteria, inhibiting most isolates of the family Enterobacteriaceae at concentrations of less than or equal to 4 micrograms/ml, but were not active against Acinetobacter species, most Pseudomonas species, Campylobacter jejuni, and Flavobacterium meningosepticum. Ceftetrame was also more active than cephalexin against most streptococcal isolates and as active as cephalexin against methicillin-susceptible Staphylococcus aureus; against the latter cefetamet was ineffective.